Detection and Monitoring Intra/Inter Crosstalk in Optical Network on Chip - Ahmed Jedidi (Institute of Advanced Engineering and Science, 2018)
Multiprocessor system-on-chip (MPSoC) has become an attractive solution for improving the performance of single chip in objective to satisfy the performance growing exponentially of the computer applications as multimedia applications. However, the communication between the different processors’ cores presents the first challenge front the high performance of MPSoC. Besides, Network on Chip (NoC) is among the most prominent solution for handling the on-chip communication. Besides, NoC potential limited by physical limitation, power consumption, latency and bandwidth in the both case: increasing data exchange or scalability of Multicores. Optical communication offers a wider bandwidth and lower power consumption, based on, a new technology named Optical Network-on-Chip (ONoC) has been introduced in MPSoC. However, ONoC components induce the crosstalk noise in the network on both forms intra/inter crosstalk. This serious problem deteriorates the quality of signals and degrades network performance. As a result, detection and monitoring the impairments becoming a challenge to keep the performance in the ONoC. In this article, we propose a new system to detect and monitor the crosstalk noise in ONoC. Particularly, we present an analytic model of intra/inter crosstalk at the optical devices. Then, we evaluate these impairments in objective to present the motivation to detect and monitor crosstalk in ONoC, in which our system has the capability to detect, to localize, and to monitor the crosstalk noise in the whole network. This system offers high reliability, scalability and efficiency with time running time less than 20 ms.